2020
DOI: 10.3390/plants9111609
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Antidiabetic Activity of Methanolic Extract of Punica granatum Leaves in Nicotinamide/Streptozotocin-Induced Type 2 Diabetes in Rats

Abstract: The current study aimed to establish the mechanisms of antidiabetic activity of methanolic extract of Punica granatum leaves (MEPGL) in nicotinamide/streptozotocin-induced type 2 diabetes in rats. Phytochemical screening, HPLC analysis, and acute toxicity study of MEPGL were carried out. Various concentrations of MEPGL (100, 200, 400, and 600 mg/kg) were administered orally to diabetic rats for 45 days on a daily basis. The antidiabetic effect of MEPGL was examined by measuring blood glucose, plasma insulin, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 55 publications
(60 reference statements)
5
17
0
Order By: Relevance
“…As shown in Table 3 , the r value of PCC demonstrated a positive significant correlation of TFs and CTs with radical scavenging and ferric reducing activities orderly measured by ABTS ( r = 0.98, r = 0.99), DPPH ( r = 0.89, r = 0.83), and FRAP ( r = 0.94, r = 0.86), respectively, indicating that the evolution of these phenolic compounds significantly contributed to the good antioxidant stability of PLI during one-day storage. This observation was strengthened by several studies [ 17 , 41 ] reporting that the antioxidant and anti-diabetic activity of PL extracts was linked to the presence of flavonoids and tannins.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…As shown in Table 3 , the r value of PCC demonstrated a positive significant correlation of TFs and CTs with radical scavenging and ferric reducing activities orderly measured by ABTS ( r = 0.98, r = 0.99), DPPH ( r = 0.89, r = 0.83), and FRAP ( r = 0.94, r = 0.86), respectively, indicating that the evolution of these phenolic compounds significantly contributed to the good antioxidant stability of PLI during one-day storage. This observation was strengthened by several studies [ 17 , 41 ] reporting that the antioxidant and anti-diabetic activity of PL extracts was linked to the presence of flavonoids and tannins.…”
Section: Resultsmentioning
confidence: 86%
“…Currently, some putative remedies of PLs can include the inhibition of microbial and inflammation [ 15 , 16 , 17 ]. Nevertheless, knowledge of the bioactive substances and the biological characteristics of pomegranate leaf infusion (PLI) remains scarce, including knowledge of the possible degradation of the polyphenolic composition and antioxidant capacity during 24 h of storage.…”
Section: Introductionmentioning
confidence: 99%
“…The role of GMC is to stimulate insulin secretion by pancreatic beta cells, and this ensure sufficient glucose uptake into cells. GMC was also reported to inhibit the initiation of lipid peroxide (LPO) formation when insufficient uptake occurred (Erejuwa et al 2010, Rabbani et al 2010, Obi et al 2015, Pandarekandy et al 2017, Pottathil et al 2020. Enhancement of lipid peroxide (LPO) was monitored through MDA as its main product.…”
Section: Antihyperglycemic and Antioxidant Effect Of Ibl Extractmentioning
confidence: 99%
“…Many studies reported that anthocyanin has potential an antidiabetic agent (Matsui et al 2002, Jayaprakasam et al 2005, Olivas-Aguirre et al 2016, Khoo et al 2017, Luo et al 2018, Al-Yousef et al 2020, Vilhena et al 2020. Their antihyperglycemic potency is presumed to be due to inhibition of oxidative stress, which leads to induction of pancreatic beta cells to produce sufficient insulin level (Vessal et al 2003, Jawi et al 2009, Pottathil et al 2020.…”
Section: Introductionmentioning
confidence: 99%
“…These doses were chosen for this study based on the results of previous toxicological studies [19][20][21].…”
Section: Polyphenol Contentmentioning
confidence: 99%